Association between α‐adducin rs4961 polymorphism and hypertension: A meta‐analysis based on 40 432 subjects - Jin, Hongyan; Huang, Yupeng; Yang, Guokang (Journal of cellular biochemistry, 2019)
Background: Recently, the role of α‐adducin rs4961 polymorphism in hypertension (HTN) was intensively analyzed, but the results of these studies were inconsistent. Therefore, we performed this study to better assess the relationship between α‐adducin rs4961 polymorphism and the likelihood of HTN. Methods: Eligible studies were searched in PubMed, Medline, Embase, and Web of Science. Odds ratios with 95% confidence intervals were used to assess the relationship between α‐adducin rs4961 polymorphism and HTN. Results: A total of 33 studies with 40 432 participants were analyzed. Significant associations with the likelihood of HTN were detected for the α‐adducin rs4961 polymorphism with fixed effect models (FEM) (dominant model: P = 0.003; allele model: P = 0.003), but not with random effect models (REM). Further subgroup analysis according to ethnicity of participants revealed that the α‐adducin rs4961 polymorphism was significantly associated with the likelihood of HTN in Asians (7721 cases and 8299 controls) with both FEMs (dominant model: P < 0.0001; additive model: P = 0.01; allele model: P < 0.0001) and REMs (dominant model: P = 0.0005; additive model: P = 0.03; allele model: P = 0.0006). Conclusions: Our findings indicate that the α‐adducin rs4961 polymorphism may serve as a genetic biomarker of HTN in Asians. This is so far the largest evidence‐based meta‐analysis on ɑ‐adducin polymorphism and hypertension (HTN). Our findings indicated that the ɑ‐adducin rs4916 polymorphism may serve as a genetic biomarker of HTN in Asians. Future investigations are needed to explore the potential roles of other ɑ‐adducin gene polymorphisms in the development of HTN.